Everyday Religious Tolerance in Gampong Keude Siblah: Social Practices and Symbolic Boundaries between Chinese-Indonesian and Muslim Communities - Muhammad Muhammad; Nayla Khusnia; Fadlan Barakah (Sinthop)
This study explores religious tolerance between the Chinese-Indonesian and Muslim communities in Keude Siblah Village, Southwest Aceh. Using a qualitative case study approach, the research draws on in-depth interviews, participant observation, and documentation. The findings reveal that religious tolerance in this village is a lived reality, visible in shared participation in village activities, mutual respect for religious holidays, and inclusive social solidarity. Rather than stemming from formal regulations, this tolerance has evolved through long-standing symbolic interactions rooted in local history and culture. Local institutions—including the village government, customary councils, religious leaders, and women’s groups—play essential roles in sustaining social harmony. However, minority religious expressions remain culturally constrained, often practiced in private. The main challenges include limited structural representation for the Chinese community and increasing intolerance among youth influenced by digital media. The study concludes that local religious tolerance is a negotiated social construct that requires structural support to be sustained. The findings highlight the need to integrate multicultural values into village policies and local education.